Fulvic-iron synergy enhances sediment iron-bound phosphorus immobilization and organic pollutant removal with electrode intervention - Wang, Hao (Environmental technology, 2025)
Excessive phosphorus discharge into lacustrine systems was recognized as a primary factor for eutrophication, significantly disrupting the ecological equilibrium of freshwater ecosystems. Effectively controlling endogenous phosphorus release from sediment reservoirs constitutes a fundamental prerequisite for mitigating this environmental challenge. In this study, a sediment microbial fuel cell (SMFC) was developed to address the challenges of sediment-bound phosphorus mobilization. Sediment Total Organic Carbon (TOC) removal in CC-FA-0.2 yielded 2.25 times greater than the control, indicative of aromatic and fulvic acid degradation. Phosphorus in interstitial water decreased by 66% in closed-circuit (CC) reactors, with sequential fractionation revealing enhanced iron-bound phosphorus (BD-P) retention in sediment (105% increase in CC-FA-0.05 vs. versus control). Fe(Ⅲ) redox cycling under SMFC operation maintained higher Fe(Ⅲ) retention (58-54% vs. 51-52% in open-circuit), critical for phosphate immobilization. Microbial profiling identified Proteobacteria (20.41%) and Desulfobacterota (20.41%) as dominant phyla, with genera like Geobacter and Sideroxydans synergistically driving Fe(Ⅲ)/Fe(Ⅱ) cycling and extracellular electron transfer. This study establishes a novel bioelectrochemical strategy based on fulvic-iron synergy, which drive a sustainable electrode-iron-humus redox cycle. This process offers a highly effective and sustainable approach for the simultaneous immobilization of sediment phosphorus and removal of organic pollutants in situ